Health service factors that affect adherence to tuberculosis treatment in Ghana - Salifu, Yakubu; Eliason, Cecilai; Mensah, George (RCN Publishing, 2018)
Most of the global cases of tuberculosis (TB) are found in Asia and Africa. This is largely due to deficient educational information, myths, beliefs and suboptimal service delivery as a result of inadequate infrastructure. Even though proper treatment can cure TB, bureaucratic difficulties and problems with caring for patients mean procedures to ensure that patients receive and complete treatment may stifle the treatment regimen.